Penguatan nilai Moderasi Beragama pada Kurikulum Merdeka di Sekolah Dasar - Anik Sunariyah; Imam Mawardi (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2024)
Islamic Religious Education in the independent curriculum has an important role in shaping the character of students who are tolerant and respectful of diversity. Therefore, the values of religious moderation should be instilled in students from an early age. Through an independent curriculum can help children understand and accept differences, which in turn builds a strong social foundation. This type of research is qualitative research where researchers describe the findings obtained related to strengthening the values of religious moderation through the implementation of the independent curriculum. The results of this study indicate that strengthening the values of religious moderation through the implementation of the independent curriculum is carried out in Islamic Religious Education learning to form good attitudes and personalities with noble character and carry out religious teachings. The learning is referring to the Pancasila student profile, where there are six dimensions related to religious moderation, namely; faith and piety in God Almighty and noble character; independent; mutual cooperation; global diversity; critical reasoning; and creative.